QUALITATIVE RESEARCH IN FORENSIC MEDICINE IN INDONESIA: SCOPING REVIEW OF THE CURRENT SITUATION AND POTENTIAL FOR IMPROVING EVIDENCE-BASED PRACTICE - mahendra, temmy (Jurnal Forensik dan Medikolegal Indonesia, 2020)
Purpose: Research is one of the most important efforts to increase evidence-based practice (EBP) in the field of medicine, including forensic medicine. Of the various existing research methods, qualitative methods have not been widely used in forensic medicine, especially in Indonesia. This study aims at determining the current situation of the use of qualitative research methods in forensic medicine in Indonesia and their potential application in increasing EBP. Methods: This study is a scoping review using electronic search engines and databases with various combinations of keywords related to qualitative research methods and forensic medicine. The search was carried out on keywords in the titles and abstracts of published scientific papers, both in Indonesian journals and foreign journals written by Indonesian authors. The advantages, disadvantages, potentials, challenges, and barriers to the use of qualitative research methods in forensic medicine are also discussed. Results: Qualitative research methods have not been widely used in the field of forensic medicine in Indonesia. Qualitative methods can be useful in researching topics that require more profound exploration of a phenomenon and its influencing factors, especially in studying new phenomena. Potential bias can indeed occur because of the relatively more prominent role of the researcher in data collection and interpretation, but this can be overcome by using research techniques that maintain scientific rigor. Conclusion: There is still a vast potential for qualitative research to improve EBP in forensic medicine in Indonesia.